G‐space versus E‐space: Are hornets (Hymenoptera: Vespidae) at equilibrium with honeybees in Asia? - Ehsan Rahimi; Chuleui Jung (Ecology and Evolution)
Abstract This study delves into the concept of niche conservatism (NC) and its implications for how hornets (Hymenoptera: Vespidae) and honeybees respond to climate change. Our primary objectives are threefold: firstly, to assess whether distinct environmental niche spaces (E‐space) exist between 12 hornets and honeybees like Apis cerana and Apis mellifera in Asia; Secondly, to explore the degree to which Asian hornets have attained geographic equilibrium alongside honeybee species. Lastly, is to investigate how the geographic niche overlap (G‐space) between hornets and honeybees could potentially change under climate change scenarios. To accomplish these goals, we employed ordination and ecological niche modeling techniques to analyze 91 pairs of hornets and honeybees in both geographic (G‐space) and environmental (E‐space) contexts. Then, we projected the potential impacts of climate change on the future geographic overlap between hornets and honeybees, specifically under the SSP585 climate scenario for the year 2070. Our results demonstrated that the environmental niches (E‐space) of hornets and honeybees can be treated as interchangeable, indicating they have similar environmental preferences despite being unrelated taxa. We found that Vespa velutina currently exhibits a moderate geographic niche overlap (G‐space) of 0.63 with both honeybee species. Meanwhile, Vespa mandarinia demonstrates an overlap of 0.46 with Apis cerana and 0.63 with Apis mellifera. The overlap of Vespa velutina with Apis cerana might potentially decrease to 0.51 and 0.56 with Apis mellifera. For Vespa mandarinia, the overlap could reach 0.41 with Apis cerana and 0.6 with Apis mellifera under a climate change scenario. This study indicates that the limited spatial overlap between honeybees and hornets across certain areas in Asia is more likely influenced by geographical barriers rather than solely environmental unsuitability for hornets. In this study, we delve into the concept of niche conservatism (NC) and its implications for how hornets (Hymenoptera: Vespidae) and honeybees respond to climate change.